Silence of God in Suffering: A Theological Reflection on Judges 6:13 and the Book of Job in the Face of Biblical Theology (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Divine silence in the context of human suffering, drawing primarily from Judges 6:13 and the Book of Job, both texts present profound theological challenges as they depict individuals grappling with the perceived absence of God amidst deep affliction. Gideon's lament “If the Lord is with us, why then has all this happened to us?” echoes Job's prolonged agony and unanswered questions. Rather than providing direct answers, these biblical narratives reveal a theological pattern where silence is not equivalent to divine absence but becomes a medium for testing, transformation, and deeper trust. This study situates these texts within the broader framework of biblical theology, arguing that divine silence serves as a formative experience that shapes faith, exposes the limitations of human understanding, and calls for a resilient, relational trust in God. Furthermore, the article reflects on the contemporary relevance of these themes, particularly in the Nigerian context, where many Christians face ongoing socio-political and economic suffering. It concludes that divine silence, while disorienting, can become a profound space for lament, dialogue, and spiritual growth when viewed through the lens of Scripture.